Outlander. The complete seventh season [videorecording (DVD)] - Moore, Ronald D. (Sony Pictures Home Entertainment, 2025)
After serving as a British Army nurse in World War II, Claire Randall is enjoying a second honeymoon in Scotland with husband Frank, an MI6 officer looking forward to a new career as an Oxford historian. Suddenly, Claire is transported to 1743 and into a mysterious world where her freedom and life are threatened. To survive, she marries Jamie Fraser, a strapping Scots warrior with a complicated past and a disarming sense of humor. A passionate relationship ensues, and Claire is caught between two vastly different men in two inharmonious lives.